Concealed Information Test with Combination of ERP Recording and Autonomic Measurements - Farahani, E.D.; Moradi, M.H.A. (Нейрофизиология, 2013)
The concealed information test (CIT) is based on a comparison between the subject’s physiological responses to a probe and irrelevant items in order to detect concealed information. The main purpose of our study was to investigate the CIT accuracy enhancement related to a combination of recording of event-related potentials (ERPs) and autonomic measurements. We tried to maximally liken the experimental conditions to real ones by the use of a criminal context in the “mock crime” instruction and real innocent subjects instead of hypothetical ones. Fifty-two subjects volunteered and performed just one of the innocent or guilty scenarios. The CIT was designed in five blocks with short interstimulus intervals. In each block, stimuli were presented in the 7th-order balanced sequence. In addition to EEG phenomena, the heart rate, skin conductance responses (SCRs), respiratory activity, and finger plethysmogram were recorded. Statistical analyses showed that there was a significant difference between standardized difference scores of the guilty and innocent groups in both ERP and autonomic measures. The SCR did not achieve the expected results reported in standard autonomic-based CIT studies. A review of the two classification methods showed that the combination of ERP and autonomic measurements enhances the CIT accuracy. The best classification accuracy obtained by the aid of linear discriminant analysis (LDA) was 90.9%. It seems that using a criminal context in the “mock crime” instruction and the rewardpunishment system made subjects more attentive and involved in the experiment; therefore, the accuracy was improved compared with that in similar studies